Dynamics of career development of Giriloyo batik makers - Nur Hasanah (Department of Psychology, Universitas Negeri Yogyakarta, 2019)
The purpose of this study is to describe the dynamics of the career development on each stage, starting from growth, exploration and establishment in Batik makers of Giriloyo. This study employs case study qualitative research methods, and involves three women who worked as batik maker. Data analysis was performed by data reduction, data presentation, and conclusion drawing. From this research it is revealed that participants did not fulfill the developmental tasks at all three stages as a whole and they went through stages of career development sequences and period that is differed from the established theory of career development. It is also revealed that the participants experienced dissatisfaction with the wages. However, in the other hand they felt proud to be able to take part on their community and wishes to continue to make batik as long as they are physically able. The results of the study led researchers to recommend early career recognition by families, schools and communities.